In Situ Contact-Separation TENG for High-Speed Rail Wind Monitoring - Guangzheng Wang; Depeng Fu; Yuankun Li; Xiaoxiong Wang (Nanomaterials)
Triboelectric nanogenerators have attracted extensive attention as they can complete sensing during energy conversion, triggering a series of self-powered designs. Traditional TENG bipolar independent fabrication technology requires secondary motion control, which limits its application scenarios. In this work, we propose a flag-type TENG prepared using in situ electrospinning technology, in which the connecting region is obtained by electrospinning deposition of PVDF on nylon as the receiving electrode. The active area is isolated with silicone oil paper. After electrospinning, the silicone oil paper was removed, and the distance between the nylon and PVDF is far beyond the van der Waals range. Thus, contact separation can be effectively carried out under the action of wind. The device has been proven to be able to be used for monitoring wind conditions at high-speed rail stations and enables completely self-powered monitoring of the wind level using self-powered LED coding. The device no longer relies on additional batteries or wires to work, providing additional ideas for future self-powered system design.